HUBUNGAN KADAR ALBUMIN SERUM DENGAN KELUARAN PASIEN STROKE ISKEMIK AKUT - Taufik Mesiano*, Salim Harris*, Al Rasyid* (NEURONA, 2010)
INTRODUCTION ALBUMIN IN BLOOD HAS VARIOUS IMPORTANT FUNCTIONS ITS LEVEL DECREASED AS RESPONSE TO ACUTE INFLAMATION THAT ALSO OCCURS IN ACUTE ISCHEMIC STROKE DECREASE IN SERUM ALBUMIN LEVEL HYPOALBUMIN WILL AFFECT THE OUTCOME OF ACUTE ISCHEMIC STROKE PATIENT